Current and Future Treatments in Alzheimer's Disease - Atri, Alireza (Seminars in Neurology, 2019)
The foundation of current Alzheimer's disease (AD) treatment involves pharmacological and nonpharmacological management and care planning predicated on patient-centered psychoeducation, shared goal-setting, and decision-making forged by a strong triadic relationship between clinician and the patient-caregiver dyad. Food and Drug Administration (FDA) approved AD medications, cholinesterase-inhibitors (ChEIs), and the N-methyl-d-aspartate (NMDA) antagonist memantine, when utilized as part of a comprehensive care plan, while generally considered symptomatic medications, can provide modest “disease course-modifying” effects by enhancing cognition, and reducing loss of independence. When combined, pharmacologic and nonpharmacologic treatments can meaningfully mitigate symptoms and reduce clinical progression and care burden. AD pharmacotherapy first involves identification and elimination of potentially harmful medications and supplements. First line treatment for neuropsychiatric symptoms and problem behaviors is nonpharmacological and involves psychoeducation, trigger identification, and implementation, iterative evaluation, and adjustment of behavioral and environmental interventions. Intensive research efforts are underway to develop more accurate and practical AD diagnostic biomarkers and clinical tools and better therapeutics. Ongoing research studies for primary and secondary prevention of AD and clinical trials evaluating symptomatic and disease-modifying treatments in symptomatic AD are directed at diverse therapeutic targets including neurochemicals, amyloid and tau pathological processes, mitochondria, inflammatory pathways, neuroglia, and multimodal lifestyle interventions.
Keywords: cognitive impairment; dementia; cholinesterase-inhibitor